Childhood Psychosocial Adversity and Adult Neighborhood Disadvantage as Predictors of Cardiovascular Disease: A Cohort Study. Issue 5 (4th August 2015) - Halonen, Jaana I.; Stenholm, Sari; Pentti, Jaana; Kawachi, Ichiro; Subramanian, S.V.; Kivimäki, Mika; Vahtera, Jussi
Abstract : Background—: Childhood adverse psychosocial factors (eg, parental divorce, long-term financial difficulties) and adult neighborhood disadvantage have both been linked to increased cardiovascular disease (CVD). However, their combined effects on disease risk are not known. Methods and Results—: Participants were 37 699 adults from the Finnish Public Sector study whose data were linked to a national neighborhood disadvantage grid with the use of residential addresses between the years 2000 and 2008 and who responded to a survey on childhood psychosocial adversities and adult CVD risk behaviors in 2008 to 2009. Survey data were also linked to national registers on hospitalization, mortality, and prescriptions to assess CVD risk factors in 2008 to 2009 and to ascertain incident CVD (coronary heart disease or cerebrovascular disease) between the survey and the end of December 2011 (mean follow-up, 2.94 years; SD=0.44 years). Combined exposure to high childhood adversity and high adult disadvantage was associated with CVD risk factors (hypertension, dyslipidemia, diabetes mellitus, obesity, smoking, heavy alcohol use, and physical inactivity) and with a 2.25-fold (95% confidence interval, 1.39–3.63) hazard of incident CVD compared with a low childhood adversity and low adult disadvantage. This hazard ratio was attenuated by 16.6% but remained statistically significant after adjustment for the CVD risk factors (1.96; 95% confidence interval, 1.22–3.16). Exposure to high childhood adversity or high adult neighborhood disadvantage alone was not significantly associated with CVD in fully adjusted models. Conclusions—: These findings suggest that individuals with both childhood psychosocial adversity and adult neighborhood disadvantage are at an increased risk of CVD. In contrast, those with only 1 of these exposures have little or no excess risk after controlling for conventional risk factors. Abstract : Supplemental Digital Content is available in the text.